Formulasi Glowing Acne Cream Ekstrak Daun Nipah (Nypa fruticans) Sebagai Produk Untuk Mencegah Pertumbuhan Jerawat Dan Memperbaiki Skin Barrier - Adillah, Fadya; Mursyid, Murni; Astari, Chitra; Rahmah, Andi Fikrah; Muthmainnah, Nur Hikmah; Fadila, Nikma (Program Studi Farmasi Universitas Mandala Waluya, 2024)
One of the skin problems that often occurs among teenagers today is acne. Acne treatment generally uses antibiotics which can have side effects in the form of irritation or resistance if used long term. Therefore, another alternative is needed in treating acne, namely using natural ingredients which are expected to minimize the side effects of using antibiotics. A natural ingredient that is efficacious as an acne medicine is nipah leaves (Nypa fruticans) which contain flavonoid compounds which function as antibacterial agents. The aim of this research is to determine the physical properties test and at what concentration the glowing acne cream preparation of nipah leaf extract (Nypa fruticans) is effective against Propionibacterium acnes bacteria. The research results showed that the organoleptic test, homogeneity test, pH test, spreadability test, stickiness test, cream type test, viscosity test had fulfilled the preparation evaluation requirements. In the irritation test for all formulas all respondents had negative results and in the hedonic test for F1 color was preferred, aroma and shape were preferred by respondents in F2. Meanwhile, in the antibacterial activity test for the very strong category, it was found in F1 with an inhibitory zone diameter of 20.16mm and for the results of statistical analysis using one way ANOVA, the value P=0.000 was obtained